2022
DOI: 10.1002/gj.4562
|View full text |Cite
|
Sign up to set email alerts
|

Ore genetic implications of pyrite and sphalerite compositions fromRajpura‐Daribaand ZawarmalaPb‐Zndeposits, Northwestern India

Abstract: We have studied different generations of pyrite (Py-I, II and III) and sphalerite (Sph-I, II and III), associated with ore mineralization and remobilization stages, from both the deposits. In Rajpura-Dariba, high concentrations of the majority of trace elements in syngenetic Py-I and Sph-I suggest their formation from trace element enriched hydrothermal fluid in SEDEX environment. Enrichment of lattice bound elements in Py-II (As, Co, Ni) and Sph-II (Mn, Hg and Cd) during metamorphic recrystallization of early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 106 publications
0
0
0
Order By: Relevance
“…11). This variety of ore (sphalerite and pyrite) is poor in trace elements and considered to be diagenetic and suggests that the initial ore-forming fluid was depleted in several trace elements (Bhuyan & Hazarika 2022). In this variety, diagenetic microstructures preserved in low strain zones, are represented by pyrite frambroids (Fig.…”
Section: Mineralizationmentioning
confidence: 93%
See 4 more Smart Citations
“…11). This variety of ore (sphalerite and pyrite) is poor in trace elements and considered to be diagenetic and suggests that the initial ore-forming fluid was depleted in several trace elements (Bhuyan & Hazarika 2022). In this variety, diagenetic microstructures preserved in low strain zones, are represented by pyrite frambroids (Fig.…”
Section: Mineralizationmentioning
confidence: 93%
“…Mukherjee & Sen (1980) indicated low REE in the carbonate assemblages and concluded that the deposit was formed under Bhuyan & Hazarika (2022), temperature data from Tallari et al, (2000). (Chakrabarti, 1966).…”
Section: Geochemical and Geobotanical Signaturesmentioning
confidence: 99%
See 3 more Smart Citations